Navigating Hypersexuality in Bipolar: Insights from a Corpus-Assisted Discourse Analysis of Reddit Posts - Daisy Harvey PhD; Paul Rayson PhD; Fiona Lobban PhD; Jasper Palmier-Claus PhD; Clare Dolman PhD; Steven Jones PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Bipolar is a severe mental health condition affecting at least 2% of the global population. Clinical observations indicate that individuals in elevated mood states, such as mania or hypomania, are more likely to engage in risk-taking behaviours, including hypersexuality. Characterised by an excessive preoccupation with sex, hypersexuality can lead to serious consequences such as sexual assault, unplanned pregnancies, and relationship breakdowns. Existing evidence suggests that opportunities for intervention in cases of hypersexuality in bipolar may currently be overlooked. This study provides insight into the lived experience of hypersexuality in bipolar using corpus-assisted discourse analysis (CADA) to qualitatively examine Reddit posts. The use of Reddit as a source of information in this study is particularly valuable because Reddit posts include narratives that may not be captured in traditional clinical settings. The candid, community-driven discussions found on Reddit can help identify gaps in care and raise awareness of the nuanced ways in which hypersexuality manifests and impacts individuals. Analysis of Reddit posts enables researchers to explore patterns, themes, and concerns that may be overlooked or underreported in clinical research, offering a more comprehensive understanding of the symptom of hypersexuality in bipolar. By employing keyword, concordance, and collocation methods, we identified 14 key thematic categories within the corpus and explored 4 of these in greater detail. The analysis showed that Redditors discussed hypersexuality within the context of bipolar symptoms, with many terms related to mood fluctuations and associated emotions. The diverse language used to describe sexual behaviours, along with references to shame and judgement, highlighted significant issues surrounding the discussion of hypersexuality in society and within healthcare settings. To enhance clinical practice, discussions about hypersexuality should be normalised and integrated into routine assessments, and healthcare professionals should receive training to address stigma.